Editor’s introduction: Applied qualitative research - Mariaelena Bartesaghi (Qualitative Research in Medicine & Healthcare)
The works in this issue, whether directly or indirectly, speak to the invaluable role of qualitative inquiry in offering viable solutions or alternative affordances for the practices that are studied. (...)